An entangled history of postcolonial and socialist education: institutional transfer for educational equality and national development. (4th May 2021) - Kaiser, Tim; Miethe, Ingrid; Piepiorka, Alexandra; Kriele, Tobias
ABSTRACT: Searching for development paths and suitable educational policies, postcolonial governments often turned to the experiences of other countries and sought to adapt these to their own contexts. Research on such processes has largely neglected the resulting entanglements between postcolonial and European socialist countries, and between different postcolonial countries. This gap in research is addressed in this article by tracing a world-spanning history of educational transfers that has its origins in the Workers' Faculties of the early Soviet Union. Workers' Faculties were established with two goals: quickly channelling members of formerly disadvantaged social groups into higher education by providing university-preparatory education to workers and peasants; and providing suitably educated cadres for the development of a socialist society. After World War 2, institutions drawing on the Soviet experiences and combining these two goals were established in European, Asian, Latin American, and African countries. Tracing the processes of transfers and local interpretations of these institutions gives insights into an entangled history of postcolonial and socialist education, but also into how tensions between education as a means to provide social equality and education as a tool for (socialist) development played out in various national contexts.